The Influence of PAKEM Model Using Tangram Media on Learning Motivation and Spatial Mathematical Ability of Grade II Students of SD IT Khalisaturrahmi Binjai - Athiyyah Zahrah Al-Fananie; Edi Syahputra; Evi Eviyanti (BIRCU, 2020)
This study aims to determine: (1) The spatial ability of students taught using the PAKEM model assisted by tangram media is higher than students taught using the expository model. (2) The learning motivation of students taught using the PAKEM model assisted by tangram media is higher than students taught using the expository model. (3) The interaction between the PAKEM learning model assisted by tangram media with the students 'initial mathematics ability towards the students' mathematical spatial abilities, and (4) The interaction between the PAKEM learning model assisted by tangram media with the students 'initial mathematics ability towards students' learning motivation. This research method is a quasi experiment. The population of this study were all students of Class II SD IT Khalisaturrahmi Binjai totaling 40 students. The research sample was Class II A (20 students), and Class II B (20 students). The instruments used consisted of the KAM test, a test of students' mathematical spatial abilities, and a student motivation questionnaire. The analysis was carried out using two-way ANOVA. The results showed that: (1) The spatial ability of students taught with the PAKEM model assisted by tangram media was higher than students taught using the expository model. (2) The learning motivation of students taught using the PAKEM model assisted by tangram media is higher than students taught using the expository model. (3) There is no interaction between learning the PAKEM model assisted by tangram media with students' initial mathematical abilities against students' mathematical spatial abilities, and (4) There is no interaction between learning the PAKEM model assisted by tangram media with students' initial mathematical abilities on student learning motivation.